Small-angle neutron scattering investigation of polyurethane aged in dry and wet air - Q. Tian; G. Yan; L. Almasy; G. Sun; X. Zhou; J. Liu; L. Rosta; B. Chen; I. Krakovsky; M. Veres (eXPRESS Polymer Letters, 2014)
The microstructures of Estane 5703 aged at 70°C in dry and wet air have been studied by small-angle neutron scattering. The samples were swollen in deuterated toluene for enhancing the contrast. The scattering data show the characteristic domain structure of polyurethanes consisting of soft and hard segments. Debye-Anderson-Brumberger function used with hard sphere structure factor, and the Teubner-Strey model are used to analyze the two-phase domain structure of the polymer. The combined effects of temperature and humidity have a strong disruption effect on the microstructures of Estane. For the sample aged at 70°C in wet air for 1 month, the domain size, described by the correlation length, increases from 2.3 to 3.8 nm and their distance, expressed by hard-sphere interaction radius, increases from 8.4 to 10.6 nm. The structure development is attributed to degradation of polymer chains as revealed by gel permeation chromatography. The hydrolysis of ester links on polymer backbone at 70°C in the presence of water humidity is the main reason for the changes of the microstructure. These findings can contribute to developing predictive models for the safety, performance, and lifetime of polyurethanes.